IKLIM ORGANISASI DAN PENGARUHNYA TERHADAP KEPUASAN KERJA PEGAWAI PUSKESMAS GONDANGLEGI MALANG - Supriadi Supriadi (Jurnal Akademika, 2005)
This research was subjected to analysis the climats organizations that influence the working satisfactions of employee at the Puskesmas Gindanglegi of Malang. Taking sample method was used sensus, remember that the amount of population in research place was not much. The amount of the employees seen in research was 25 employee. By using this multiple regretion method, research result that all independent variable in organization climates consists of leader behavior variable, working motivation, communication stream, interaction and taking decision which effected positif actual employee satisfaction. keyword; Climates Organization, Working Satisfaction.